First data about the preimaginal morphology of Austroscaeva occidentalis (Shannon, 1927) and re‐description of larvae and pupae of Dioprosopa clavata (Fabricius, 1794) (Diptera: Syrphidae). Issue 3 (7th June 2021) - Lillo, Inés; Pérez‐Bañón, Celeste; Arcaya, Evelin; Mengual, Ximo; Rojo, Santos
Abstract: Preimaginal morphology of Austroscaeva occidentalis (Shannon, 1927) is described for the first time, and the morphology of larvae and pupae of Dioprosopa clavata (Fabricius, 1794) is updated based on material obtained from captive rearing of wild females from Argentina and Venezuela, respectively. We describe the morphology of the third instar larva, head skeleton and puparium using optical microscopy, cryo‐scanning and scanning electron microscope. The immature stages of both New World flower fly species are analysed and compared with the known preimaginal morphology of other taxa that belong to the evolutionary lineage of Eupeodes‐Scaeva, where Austroscaeva Láska, Mazánek & Mengual, 2018, and Dioprosopa Hull, 1949, form a Neotropical radiation within, together with the genus Notosyrphus Vockeroth, 1969. Larvae of all members of this lineage have abdominal segments 5 and 6 with the tips of the locomotory prominences facing posteriorly, and the anal segment with a characteristic U‐shaped grasping organ. Two other larval synapomorphies of this group of genera are the presence of metathoracic setae accompanying ventral sensilla, and the abdominal segments 1–7 with an extra lobe on each locomotory prominence. These two last characters cannot be assessed for Macrosyrphus Matsumura, 1917, and Lapposyrphus Dušek & Láska, 1967, based on published information on larval descriptions. Despite a similar colouration pattern of the fully grown larvae, larval morphology of A. occidentalis and D. clavata are quite distinct. The preimaginal morphology of A. occidentalis has a mixture of morphological characters from the taxa Scaeva Fabricius, 1805, Semiscaeva Kuznetzov, 1985, and Dioprosopa . The larvae of D. clavata show several unique diagnostic features, such as the presence of a slightly serrate outline due to the great development of the segmental spines and a pinnate ornamentation of the setae of its dorsal and dorsolateral sensilla. Regarding their biological cycle, the length of the preadult stages of A. occidentalis is almost 5 days longer than the length observed for D. clavata . In addition, new DNA barcodes are provided for A. occidentalis .